Balinese Language in the Context of Early Childhood Learning - Ni Gusti Ayu Made Yeni Lestari; Endry Boeriswati; Nurbiana Dhieni (International Conferences on Early Childhood Education Proceedings, 2024)
Language is a very important aspect to be developed because it relates to the child's ability to communicate ideas and feelings. Stimulation of the language of the environment where the child lives, in this case the Balinese language also determines the child's ability to interact and communicate. This study aimed to determine the position of the Balinese language in the context of early childhood learning. The approach used in this research was descriptive qualitative. Research data were obtained through observation, interviews, and strengthened by analysis of learning documents in ECE. The total number of respondents were 7 teachers from 3 ECE institutions in Badung Regency, Bali. The data collected was then analysed using the Miles and Huberman model, which consisted of data reduction, data presentation, conclusion/verification. The results showed that: 1) the position of the Balinese language in the context of early childhood learning including second language learning, 2) Balinese language learning in ECE was intended as an effort to preserve culture for early childhood, and 3) Balinese language learning in ECE helped children easier to communicate with the environment in which he lives. The use of language by early childhood in accordance with the language of the environment in which they live, in this case is Balinese, in addition to providing opportunities for children to communicate and interact more, it can also support children's mastery of language. The more children master the language, will be better their cognitive development.